PENGARUH KETERAMPILAN MENGAJAR DAN PEMBELAJARAN MIKRO, SELF EFFICACY, DAN PERAN GURU PAMONG TERHADAP PELAKSANAAN PLP MAHASISWA PENDIDIKAN AKUNTANSI UNIVERSITAS NEGERI SURABAYA - Desy Purwantiningrum; Rochmawati Rochmawati (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
The research was conducted with the aim of determining the influence of teaching skills and microteaching, self-efficacy, and the role of teachers on the implementation of PLP for accounting education students at Surabaya State University. The research method used is a quantitative method with data collection through secondary and primary data, namely scores and questionnaires. The research population was all Accounting Education students at Surabaya State University in the in the class of 2020 who had programmed the PLP and used a saturated sample of 59 students. Data analysis was carried out using the SPSS version 26 application, with the results of the analysis stating that (1) teaching skills and microteaching, self-efficacy, and the role of teachers simultaneously have a significant influence on students' implementation of PLP. (2) Teaching skills and microteaching have a significant influence on students' PLP implementation. (3) Self-efficacy has a significant influence on students' PLP implementation. (4) The role of teachers has a significant influence on students' PLP implementation. The adjusted R square value in this study was 36.9%, which means that the contribution of teaching skills and micro-teaching, self-efficacy, and the role of teachers was 36.9%, while the remaining 63.1% was influenced by other variables outside of this research.Keywords: PLP; teaching skills and micro teaching; self efficacy; the role of teachers